“Under The Sign of a Hornless Cow...” – Revisiting the Osteological Collection from the Gorny Settlement - Ekaterina E. Antipina (Археология евразийских степей, 2022)
The author discusses the most striking and unusual features of the osteological collection from the excavations of the Gorny settlement of miners and metallurgists. These are the biological features of cattle (Bos taurus), first of all, the hornlessness (the natural absence of horns), and the specific artificial fragmentation of the bones of these animals. The mass content of the remains of hornless cow skulls with single finds of horned animals has been recorded; the calculations provided a ratio of 150 hornless cows to 1 horned specimen. This and other factual information, given the modern data on the genetic dominance of hornlessness in large ungulates, creates a basis for asserting the use of targeted artificial selection in the cattle breeding practice of the Srubnaya community in the breeding of two cattle groups, and indicates the significant scale of this industry across the territory of the Southern Urals. The specific fraction of fragmented anatomically small limb bones of hornless cows is discussed in combination with other ritual and ceremonial activities in which the animals themselves and their skeletal remains were involved. It is emphasized that cattle were not only the main food and raw material resource, but also one of the symbolic phenomena in the ritual life of miners and metallurgists.